2019
DOI: 10.1186/s12885-019-6052-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathway activity profiling of growth factor receptor network and stemness pathways differentiates metaplastic breast cancer histological subtypes

Abstract: Background: Gene expression profiling of rare cancers has proven challenging due to limited access to patient materials and requirement of intact, non-degraded RNA for next-generation sequencing. We customized a gene expression panel compatible with degraded RNA from formalin-fixed, paraffin-embedded (FFPE) patient cancer samples and investigated its utility in pathway activity profiling in patients with metaplastic breast cancer (MpBC). Methods: Activity of various biological pathways was profiled in samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…A genomics profiling study performed by McQuerry and colleagues found that MpBC samples with mesenchymal (osteoid or chondroid) histology had increased Snail, BCL-2-like-1 protein, and Akt1 pathway activity in comparison to non-mesenchymal MpBC tumors [ 16 ]. When comparing the gene expression profiles of MpBC to TNBC tumors, MpBC tumors had more upregulation of epithelial-to-mesenchymal transition (EMT) and collagen genes, but downregulation of late cornified envelope and keratinization genes.…”
Section: Histological Organization Of Mpbcmentioning
confidence: 99%
“…A genomics profiling study performed by McQuerry and colleagues found that MpBC samples with mesenchymal (osteoid or chondroid) histology had increased Snail, BCL-2-like-1 protein, and Akt1 pathway activity in comparison to non-mesenchymal MpBC tumors [ 16 ]. When comparing the gene expression profiles of MpBC to TNBC tumors, MpBC tumors had more upregulation of epithelial-to-mesenchymal transition (EMT) and collagen genes, but downregulation of late cornified envelope and keratinization genes.…”
Section: Histological Organization Of Mpbcmentioning
confidence: 99%
“…The acquisition of a mesenchymal phenotype in MBC is associated with a switching of cadherins (from E-cadherin to N-cadherin and cadherin 11) and the downregulation of epithelial markers including not only E-cadherin ( CDH1 ), but also occludens zone 1 ( ZO1 ), desmoplakin, keratin 7, keratin 18, and keratin 19, among others [ 43 ]. In contrast, genes related to the mesenchymal phenotype, motility, migration, and formation of extracellular matrix, such as vimentin, SPARC, or different collagen types, are upregulated in MBC [ 31 , 43 , 50 , 51 , 52 ].…”
Section: Epithelial To Mesenchymal Transition In Mbcmentioning
confidence: 99%
“…EMT in MBC allows cells to acquire different phenotypes due to secondary trans-differentiation. Accordingly, different expression patterns have been reported in SpCC, SqCC, and MBCHMD with chondroid differentiation [ 5 , 52 ]. Thus, SpCC showed the downregulation of epithelial genes, such as CDH1, EPCAM, CLDN3, and CLDN8 .…”
Section: Epithelial To Mesenchymal Transition In Mbcmentioning
confidence: 99%
“…More recently, it was found that co-expression of cath-D and androgen receptor defines a TNBC subgroup with poorer overall survival (6). SPARC protein and mRNA are also overexpressed in TNBC (31,33,54), and this has been associated with poor prognosis in patients with TNBC (30,31,33). Here, we showed that high mRNA expression of CTSD and SPARC tended to be associated with shorter recurrence-free survival in a cohort of 255 patients with TNBC using an on line survival tool (39).…”
Section: Discussionmentioning
confidence: 99%
“…In different cancer types, SPARC plays an oncogenic or a tumor-suppressive role (26,27). For instance, in BC, SPARC has a pro-tumorigenic role and has been associated with worse prognosis (24,(28)(29)(30)(31)(32)(33); however, other studies reported anti-tumorigenic functions (34)(35)(36). SPARC includes three different structural and functional modules: the N-terminal acidic domain, followed by the follistatin-like domain, and the C-terminal extracellular Ca 2+ binding domain (21).…”
Section: Introductionmentioning
confidence: 99%